An exploratory study of Professional Identity in Mathematics Teacher Educator-Researchers: Applying Davey’s framework as a methodological tool - Fleet, Elizabeth Jane (2021)
This research explores the identities of Mathematics Teacher Educators and Researchers via a framework of five lenses - becoming, doing, knowing, being and belonging, proposed by Davey (2013). The framework is used throughout the research, firstly to conduct a systematic review of the research into mathematics teacher educator-researchers covering the past ten years. This reveals a diversity of research examined through each lens, much of it done by the teacher educators themselves, reflecting on their own practice. It also reveals the gaps in our knowledge about UK professionals.